Preferences on language development strategies for autistic children - Yen, Chieh-Ying (Carol) (Animo Repository, 2003)
The teaching strategies utilized by the teachers in public and private special schools are identified and compared. This study made use of the descriptive-comparative method of research. A validated researcher-made questionnaire was administered to 40 teachers coming from both the SPED public (20) and private (20) schools. The findings of the study revealed that gesture is the only teaching strategy that is used always by both groups of respondents as indicated by the mean of 4.7 for the public and 4.6 for the private school SPED teachers. Both groups seldom used technology-assisted devices as a teaching strategy. This is shown by the means of 1.63 for the public and 1.98 for the private group. Furthermore, data showed that there is no significant difference between the SPED teachers in the public and private school in terms of the strategies preferred in developing the verbal communication skills of CWA (Children with autism) as shown by the computed critical t-value of 1.68.